ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MODEL ALTMAN Z-SCORE MODIFIKASI PADA PERUSAHAAN INFRASTRUKTUR DI BEI PERIODE 2021–2025 - Marno Nugroho; Odie Andika Tidar Zakawali (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study employs a descriptive quantitative approach using the Modified Altman Z-Score model to assess the financial health and bankruptcy risk of infrastructure companies. The model utilizes four financial ratios: Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Taxes to Total Assets (X3), and Book Value of Equity to Total Liabilities (X4). The analysis is based on annual financial statements from 2021–2024 and the third-quarter (Q3) 2025 interim financial statements of eight selected companies. The results indicate significant differences in financial conditions across the infrastructure sector. State-owned construction companies, namely Waskita Karya (WSKT) and Wijaya Karya (WIKA), consistently remained in the Distress Zone, with declining Z-Score values that eventually became negative. Adhi Karya (ADHI), Pembangunan Perumahan (PTPP), and Jasa Marga (JSMR) were generally classified in the Grey Zone, reflecting vulnerable but relatively stable conditions. Meanwhile, Bukaka Teknik Utama (BUKK), Citra Marga Nusaphala Persada (CMNP), and Nusantara Infrastructure (META) consistently occupied the Safe Zone. Overall, low profitability and high debt levels were identified as the primary factors contributing to bankruptcy risk among several issuers.